In search of the working class: workers’ subjectivities and resistance in an Istanbul neighborhood - Birelma, Alpkan. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2016., 2016)
This dissertation is an urban ethnography scrutinizing workers’ subjectivities and resistance in a working class neighborhood of Istanbul, Turkey. By utiliz-ing extensive case method, it aims to listen and shed light on the cultured agency of Turkish workers. It examines the apparent docility of working-class in our era of capitalist hegemony, particularly in Turkey as one of the extreme cases of this global tendency. It also contributes to the research on remedies for that docility. By focusing on the sphere of work and drawing on an extensive field work, the research explores the issues of proletarianization, entrepreneurism, mean-ings of work, and compliance and resistance at work in a different light. It re-veals that petty entrepreneurism is key to understand the hegemony of capi-talism. It uncovers the variety of meanings that workers attribute to their work and detects four subjectivities that workers move among, namely the cras-man, the hard worker, the detached survivor, and the despiser. e dissertation discovers several aspects of the subjectivity behind com-pliance and resistance, which remains to be hidden. I disclose five dilemmas of working-class resistance, namely the dilemma of dependency, of the cras-man, of coworkers, of the small workplace and of morality. Among others my primary contribution to the literature on working class resistance is to scruti-nize the dilemmas, the hidden requirements, and the sacrifices working-class resistance involves. I argue that interests and their cognition cannot fully ex-plain working-class resistance, but it requires a moral choice rather than merely a rational one.
Keywords: Working class -- Turkey -- İstanbul; Working class -- Turkey -- Social life and customs.; Working class -- Turkey.